Levonorgesterel releasing intra uterine system in the control of heavy menstrual bleeding. Is it an alternative to hysterectomy? - Nair, Sobha S.; Nayar, Jayashree; Kurien, Ann John; Seth, Isha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Heavy menstrual bleeding (HMB) affects 10 to 35% of women. Studies indicate LNG-IUS which releases controlled amounts of levonorgestrel (LNG) is effective in non- surgical treatment for HMB and has fewer side effects when compared to the conventional pharmacological agents. It also improves the quality of life. Levonorgesterel releasing intra uterine system can be an alternative to hysterectomy in the control of HMB. Methods: Retrospective study of 2 years in a tertiary care centre, Kochi. 170 women with abnormal uterine bleeding were enrolled in the study. Clinical examination, routine investigations and imaging was done. Endometrial sampling done and followed with HPE reports in indicated cases. Results: Mean age was 41 years. 30.6% had menorrhagia. Adenomyosis in 44% and endometrial hyperplasia in 19. 4%. Lost follow up in 12.9% cases and expulsion in 3.6%. 4.1% were unsatisfied and had hysterectomy. The uterine width in adenomyosis was significantly reduced p <0.012. The mean ET in endometrial hyperplasia cases also significantly reduced with p <0.01. Satisfaction rate was 97%. Conclusions: LNG-IUS is having a high success rate in controlling menstrual symptoms, thereby improving the quality of life and avoiding hysterectomy in women with abnormal uterine bleeding. It is highly efficient in symptomatic relief of adenomyosis and reduction in the uterine volume (width). Endometrial hyperplasia showed complete regression with LNG-IUS.